Method for identifying key components influencing hydrophobicity and structural strength of biological aggregate

Through selective enzymatic analysis experiments, the key components in aerobic granular sludge were identified, and the problems of difficulty in granulation and low stability of sludge in low-intensity water inlet were solved, and the stability improvement of sludge and the promotion of technical application were achieved, achieving the goal of environmental protection and emission reduction.

CN119510226APending Publication Date: 2025-02-25ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411430051.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Aerobic granular sludge is difficult to granulate in low-intensity water inlet, has a long start time, is prone to accidental disintegration, has low nitrogen removal efficiency, and the stability mechanism of sludge granulation and AGS is still unclear.

Method used

Through selective enzymatic lysis experiments, hydrolytic enzymes of different enzymatic lysis mechanisms were used to enzymatically dissolve aerobic sludge, and the changes in the surface characteristics of the sludge were observed, including the determination of hydrophobicity and structural strength, to identify key components that affect the hydrophobicity and structural strength of biological aggregates.

Benefits of technology

This method helps to explore the changes in key components under different operating conditions, and promotes the granulation and stability of aerobic granular sludge through hydraulic regulation strategies, promotes the application of aerobic granular sludge technology, and achieves sustainable development of environmental protection, emission reduction and cost saving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510226A_ABST
    Figure CN119510226A_ABST
Patent Text Reader

Abstract

A method for identifying key components influencing hydrophobicity and structural strength of a biological aggregate comprises the following steps: collecting mature granular sludge, carrying out enzymolysis on aerobic granular sludge by using sludge enzymatic hydrolysate prepared from hydrolase with different enzymolysis mechanisms, and then measuring sludge surface characteristics of the granular sludge subjected to enzymolysis. Comprising structural strength determination and hydrophobicity determination. According to the method, the surface characteristic change condition of the sludge is observed through selective enzymolysis of particles. According to an experimental method for studying how to identify sludge surface characteristics in the granulation maturing stage of AGS in the actual operation process, and further according to the influence of EPS components in the maturing stage on the aerobic granular sludge, which hydraulic regulation and control strategy is used for promoting granulation and stability of the aerobic granular sludge; further application of the aerobic granular sludge technology is facilitated, and sustainable development of environmental protection, emission reduction and cost saving is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sewage treatment and relates to an enzymatic hydrolysis experimental method for clarifying key components affecting the hydrophobicity and structural strength of biological aggregates. Background Art

[0002] Aerobic granular sludge (AGS) is composed of compact self-fixed microbial aggregates and is a promising innovative technology for wastewater treatment. However, its practical application is hampered by the difficulty of granulation in low-intensity influent, long startup time, unexpected disintegration, and low denitrification efficiency. The sludge granulation and AGS stabilization mechanism are still unclear. Therefore, understanding the granulation process is crucial to solving practical application problems.

[0003] Scholars have proposed a variety of hypotheses about the mechanism of sludge granulation, including the hydraulic selective pressure hypothesis, the hydrophobicity hypothesis, the extracellular polymeric substance hypothesis, the filamentous bacteria hypothesis, and the crystal nucleus hypothesis. Although the EPS hypothesis is not the only way to promote granulation, EPS does play an important role in the granulation process.

[0004] Extracellular polymeric substances (EPS) are a mixture of high molecular weight polymers secreted by microorganisms, with the main components being proteins, polysaccharides and humic acid. EPS has a significant effect on the surface properties of granular sludge, such as hydrophobicity, flocculation sedimentation, and surface charge, and plays an important role in sludge granulation and maintaining particle stability. As the main component of EPS, the gel-like structure of polysaccharides (PS) is generally considered to be the structural skeleton of aerobic granular sludge. Some negatively charged functional groups such as carboxyl and hydroxyl groups contained in PS are bridged and connected with metal ions to promote the formation of aggregates. Insoluble β-polysaccharides provide cohesion in the outer layer of the particles, protecting the structural stability and integrity of the particles. The special secondary structure and various properties of proteins (PN) are also believed to contribute to the structural strength of the particles. In addition, PS and PN can form permanent cross-links through covalent bonds or non-covalent bonds to form conjugated substances, which also play an important role in affecting the surface properties of sludge aggregates.

[0005] Previous studies have pointed out that certain glucans and proteins in extracellular polymers (EPS) play an important role in granular sludge granulation, but no clear explanation has been given for their specific key structures, so it has not been determined which specific structures in EPS affect hydrophobicity and structural strength. Using enzymatic hydrolysis experiments to treat granular sludge EPS components will help further study the structural mechanism of EPS related to granular sludge granulation. Summary of the invention

[0006] In order to overcome the shortcomings of the existing technology, the present invention provides a method for identifying key components that affect the hydrophobicity and structural strength of biological aggregates. The present invention selectively enzymatically hydrolyzes particles to observe changes in the surface characteristics of sludge. According to the actual operation process, the granulation maturity stage of AGS explores how to identify experimental methods that affect the surface characteristics of sludge, and further explores what hydraulic control strategies are used to promote the granulation and stability of aerobic granular sludge based on the influence of EPS components on aerobic granular sludge in the mature stage, which is conducive to the further application of aerobic granular sludge technology and achieves sustainable development of environmental protection, emission reduction, and cost savings.

[0007] The technical solution adopted by the present invention to solve its technical problem is:

[0008] A method for identifying key components that affect the hydrophobicity and structural strength of biological aggregates. Mature granular sludge is collected, and aerobic granular sludge is enzymatically hydrolyzed using sludge hydrolyzate prepared by hydrolases with different enzymatic mechanisms. The surface characteristics of the granular sludge after enzymatic hydrolysis, including structural strength and hydrophobicity, are then measured.

[0009] Furthermore, five hydrolases with different enzymatic hydrolysis mechanisms were prepared to selectively hydrolyze the particles and observe the changes in the surface properties of the sludge.

[0010] The five hydrolases are proteinase K, alpha-amylase, dextranase, cellulase and beta-amylase.

[0011] The aerobic granular sludge is rinsed three times in a 0.1M PBS buffer solution (pH7.2-7.4), and is evenly divided into six groups and placed in conical flasks, each of which is filled with a certain amount of wet granular sludge; then 25mL of working volume of PBS (pH5.0), proteinase K·1 enzymatic hydrolyzate, α-amylase enzymatic hydrolyzate, glucanase enzymatic hydrolyzate, cellulase enzymatic hydrolyzate, and β-amylase enzymatic hydrolyzate are respectively placed, and PBS is used as a control group; then all groups are placed in a 37°C water bath for cultivation, and shaken at a speed of 150rpm for 2h to completely mix them; then washed with a 0.1M PBS buffer solution (pH7.2-7.4) and centrifuged five times to terminate the enzymatic hydrolysis; the enzymatically hydrolyzed granular sludge is fully ground and filtered with filter paper to obtain a uniformly distributed mud cake, and its surface characteristics are measured.

[0012] The process of determining the hydrophobicity of sludge: The changes in the surface contact angles of granular sludge under different enzymatic hydrolysis conditions are compared with those of the granular sludge in the control group. The contact angle between the sludge surface and water can characterize the hydrophobicity of the sludge after enzymatic hydrolysis. The larger the contact angle of the mud-water interface, the stronger the hydrophobicity.

[0013] The contact angle measurement process is as follows: take out an appropriate amount of sludge mixture from the reactor and wash it twice by centrifugation with clean pure water; then grind the mud sample evenly and vacuum filter it through a 0.45μm membrane to form a mud cake, which is then stably placed in a 1% agar plate for 4 hours. When the mud cake is stable, place the cut strips of the test sample on a glass slide, take it out and dry it for 15 minutes, and use the static drop technique to drop a drop of 3μL on the mud cake. Use a camera fixed at the same horizontal height to take continuous flat photos from the front angle to record the shape and angle of the drop on the mud cake; the liquid dropped for each sample is measured at least 8 times, and the average value is taken after eliminating the outliers. The contact angle is obtained by processing the image using analysis software.

[0014] The sludge structural strength is determined by ultrasonic method. The sampling time is used as the horizontal coordinate and the corresponding absorbance is used as the vertical coordinate to draw the absorbance-time curve. The slope obtained is the instability coefficient. The larger the instability coefficient, the lower the structural strength of the granular sludge.

[0015] Determination process of structural strength: The particle samples to be tested are divided into 3 groups with equal mass in each group, and then enzymatic hydrolysis and washing are performed. Each sample and 25 ml of pure water are placed in a 50 ml centrifuge tube and placed in an ultrasonic water bath at 20 kHz and 65 W; the ultrasonic wave is applied intermittently with a cycle of 10 s on and 10 s off, and the treated particles are collected every 1 min and spectrophotometrically determined at 600 nm.

[0016] In the present invention, the process of the key component identification method includes the cultivation and use of mature granular sludge, the preparation of sludge enzymatic hydrolyzate, the enzymatic hydrolysis test to treat aerobic granular sludge and the determination of sludge surface characteristics.

[0017] The test sludge was taken from mature granular sludge in a laboratory mixed carbon source-fed and long-term running SBR reactor, and the sampling time was after 200 days of operation. The preparation of the sludge enzymatic solution prepared 5 different hydrolases according to different enzymatic mechanisms. For example, the structure of extracellular polysaccharides is mainly composed of α-1,4 glycosidic bonds, α-1,6 glycosidic bonds and β-1,4 glycosidic bonds connected to each other. α-amylase and β-amylase were used for enzymatic treatment in the experiment. The preparation method of the enzymatic solution is shown in Table 1.

[0018]

[0019] Table 1

[0020] The steps of the enzymatic hydrolysis test are shown in Figure 1As shown, after the aerobic granular sludge was repeatedly washed three times with buffer, it was evenly divided into six groups and placed in 100mL conical flasks. Each conical flask was added with an equal volume of sludge enzymatic solution, and the control group was added with buffer. Then, they were uniformly placed in a 37℃ water bath and shaken for 2h to fully complete the enzymatic hydrolysis. The buffer was washed again and centrifuged five times before the enzymatic hydrolysis was completed.

[0021] The beneficial effects of the present invention are mainly manifested in: exploring the differences in key components under different operating conditions and how to perform different hydraulic controls on key components under different operating conditions in order to maintain the stability of aerobic granular sludge under low-intensity water inflow; and contributing to the further application of aerobic granular sludge technology to achieve sustainable development of environmental protection, emission reduction and cost savings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the enzymatic hydrolysis process. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the accompanying drawings.

[0024] Reference Figure 1 A method for identifying key components that affect the hydrophobicity and structural strength of biological aggregates. Mature granular sludge is collected, and aerobic granular sludge is enzymatically hydrolyzed using sludge hydrolyzate prepared by hydrolases with different enzymatic mechanisms. The surface characteristics of the granular sludge after enzymatic hydrolysis, including structural strength and hydrophobicity, are then measured.

[0025] Furthermore, five hydrolases with different enzymatic mechanisms were prepared to selectively enzymatically hydrolyze the particles and observe the changes in the surface characteristics of the sludge. The five hydrolases were proteinase K, alpha-amylase, dextranase, cellulase, and beta-amylase.

[0026] The aerobic granular sludge is rinsed three times in a 0.1M PBS buffer solution (pH7.2-7.4), and is evenly divided into six groups and placed in conical flasks, each of which is filled with a certain amount of wet granular sludge; then 25mL of working volume of PBS (pH5.0), proteinase K·1 enzymatic hydrolyzate, α-amylase enzymatic hydrolyzate, glucanase enzymatic hydrolyzate, cellulase enzymatic hydrolyzate, and -amylase enzymatic hydrolyzate are respectively placed, and PBS is used as a control group; then all groups are placed in a 37°C water bath for cultivation, and shaken at a speed of 150rpm for 2h to completely mix them; then washed with a 0.1M PBS buffer solution (pH7.2-7.4) and centrifuged five times to terminate the enzymatic hydrolysis; the enzymatically hydrolyzed granular sludge is fully ground and filtered with filter paper to obtain a uniformly distributed mud cake, and its surface characteristics are measured.

[0027] The process of determining the hydrophobicity of sludge: The changes in the surface contact angles of granular sludge under different enzymatic hydrolysis conditions are compared with those of the granular sludge in the control group. The contact angle between the sludge surface and water can characterize the hydrophobicity of the sludge after enzymatic hydrolysis. The larger the contact angle of the mud-water interface, the stronger the hydrophobicity.

[0028] The contact angle measurement process is as follows: take out an appropriate amount of sludge mixture from the reactor and wash it twice by centrifugation with clean pure water; then grind the mud sample evenly and vacuum filter it through a 0.45μm membrane to form a mud cake, which is then stably placed in a 1% agar plate for 4 hours. When the mud cake is stable, place the cut strips of the test sample on a glass slide, take it out and dry it for 15 minutes, and use the static drop technique to drop a drop of 3μL on the mud cake. Use a camera fixed at the same horizontal height to take continuous flat photos from the front angle to record the shape and angle of the drop on the mud cake; the liquid dropped for each sample is measured at least 8 times, and the average value is taken after eliminating the outliers. The contact angle is obtained by processing the image using analysis software.

[0029] The sludge structural strength is determined by ultrasonic method. The sampling time is used as the horizontal coordinate and the corresponding absorbance is used as the vertical coordinate to draw the absorbance-time curve. The slope obtained is the instability coefficient. The larger the instability coefficient, the lower the structural strength of the granular sludge.

[0030] Determination process of structural strength: The particle samples to be tested are divided into 3 groups with equal mass in each group, and then enzymatic hydrolysis and washing are performed. Each sample and 25 ml of pure water are placed in a 50 ml centrifuge tube and placed in an ultrasonic water bath at 20 kHz and 65 W; the ultrasonic wave is applied intermittently with a cycle of 10 s on and 10 s off, and the treated particles are collected every 1 min and spectrophotometrically determined at 600 nm.

[0031] In this embodiment, the device used to cultivate aerobic granular sludge in the experiment is a conventional SBR reactor. The reactor is made of organic glass and is cylindrical. The effective volume is 5.6L and the operating temperature is 25±2℃. The influent water quality is as follows: COD is 500±12.4mg·L -1 , total nitrogen: 24±4.7mg·L -1 , ammonia nitrogen: 21±2.2mg·L -1 , total phosphorus: 5.7±1.3mg·L -1 .

[0032] Reference Figure 1, a method for identifying key components that affect the hydrophobicity of bioaggregates, the contact angle between sludge and water was experimentally determined. The contact angle between the sludge surface and water can characterize the hydrophobicity of the sludge after enzymatic hydrolysis. The larger the contact angle value of the mud-water interface, the stronger the hydrophobicity. The contact angle between sludge and water changed significantly after selective enzymatic hydrolysis of the EPS component. After hydrolysis by proteinase K, the contact angle value with water decreased to 73.1±1.3℃. The hydrophobicity did not decrease significantly, which may be because the intercellular hydrogen bonding in EPS has little effect. In addition, hydrolysis of PN may cause the positively charged amino groups it carries to be exposed, and the negatively charged carboxyl or carboxyl groups are neutralized. After aerobic granular sludge was hydrolyzed by glucanase or cellulase, the contact angles with water were 62.5±2.7℃ and 61.9±4.2℃, respectively. After hydrolysis by α-amylase, its contact angle value dropped to 51.0±4.0℃. After being hydrolyzed by β-amylase, the sludge showed the greatest hydrophilicity, with a contact angle of 44.1±2.4°C. This indicates that the hydrolysis of β-polysaccharide weakened the hydrophobic interaction between sludge cells and reduced the structural stability of aerobic granular sludge.

[0033] The contents described in the embodiments of this specification are merely enumerations of implementation forms of the inventive concept and are for illustrative purposes only. The protection scope of the present invention should not be considered to be limited to the specific forms described in this embodiment, and the protection scope of the present invention also extends to equivalent technical means that can be thought of by ordinary technicians in this field based on the inventive concept.

Claims

1. A method for identifying key components that affect the hydrophobicity and structural strength of bioaggregates, characterized in that: Mature granular sludge was collected, and the aerobic granular sludge was enzymatically hydrolyzed using sludge hydrolyzate prepared by hydrolytic enzymes with different enzymatic mechanisms. The surface characteristics of the granular sludge after enzymatic hydrolysis were then measured, including structural strength and hydrophobicity.

2. The method for identifying key components affecting the hydrophobicity and structural strength of bioaggregates as claimed in claim 1, characterized in that: Five hydrolases with different enzymatic hydrolysis mechanisms were prepared to selectively hydrolyze the particles and observe the changes in the surface properties of the sludge.

3. The method for identifying key components affecting the hydrophobicity and structural strength of bioaggregates as claimed in claim 2, characterized in that: The five hydrolases are proteinase K, α-amylase, glucanase, cellulase and β-amylase.

4. The method for identifying key components affecting the hydrophobicity and structural strength of bioaggregates according to any one of claims 1 to 3, characterized in that: The aerobic granular sludge is rinsed three times in a 0.1M PBS buffer solution with a pH value of 7.2-7.4, and is evenly divided into six groups and placed in conical flasks, each of which is filled with a set amount of wet granular sludge; then 25mL of working volume of PBS, proteinase K·1 enzymatic solution, α-amylase enzymatic solution, glucanase enzymatic solution, cellulase enzymatic solution, β-amylase enzymatic solution, PBS with a pH value of 5.0 are respectively placed, and PBS is used as a control group; subsequently, all groups are placed in a 37°C water bath for incubation, and shaken at a speed of 150rpm for 2h to completely mix them; then, they are washed with a 0.1M PBS buffer solution and centrifuged five times to terminate the enzymatic hydrolysis; the enzymatically hydrolyzed granular sludge is fully ground and then filtered with filter paper to obtain a uniformly distributed mud cake, and its surface characteristics are measured.

5. The method for identifying key components affecting the hydrophobicity and structural strength of bioaggregates according to any one of claims 1 to 3, characterized in that: The process of determining the hydrophobicity of sludge: The changes in the surface contact angles of granular sludge under different enzymatic hydrolysis conditions are compared with those of the granular sludge in the control group. The contact angle between the sludge surface and water can characterize the hydrophobicity of the sludge after enzymatic hydrolysis. The larger the contact angle of the mud-water interface, the stronger the hydrophobicity.

6. The method for identifying key components affecting the hydrophobicity and structural strength of bioaggregates according to any one of claims 1 to 3, characterized in that: The contact angle measurement process is as follows: take out an appropriate amount of sludge mixture from the reactor and wash it twice by centrifugation with clean pure water; then grind the mud sample evenly and vacuum filter it through a 0.45μm membrane to form a mud cake, which is then stably placed in a 1% agar plate for 4 hours. When the mud cake is stable, place the cut strips of the test sample on a glass slide, take it out and dry it for 15 minutes, and use the static drop technique to drop a drop of 3μL on the mud cake. Use a camera fixed at the same horizontal height to take continuous flat photos from the front angle to record the shape and angle of the drop on the mud cake; the liquid dropped for each sample is measured at least 8 times, and the average value is taken after eliminating the outliers. The contact angle is obtained by processing the image using analysis software.

7. The method for identifying key components affecting the hydrophobicity and structural strength of bioaggregates according to any one of claims 1 to 3, characterized in that: The sludge structural strength is determined by ultrasonic method. The sampling time is used as the horizontal coordinate and the corresponding absorbance is used as the vertical coordinate to draw the absorbance-time curve. The slope obtained is the instability coefficient. The larger the instability coefficient, the lower the structural strength of the granular sludge.

8. The method for identifying key components affecting the hydrophobicity and structural strength of bioaggregates according to any one of claims 1 to 3, characterized in that: Determination process of structural strength: The particle samples to be tested are divided into 3 groups with equal mass in each group, and then enzymatic hydrolysis and washing are performed. Each sample and 25 ml of pure water are placed in a 50 ml centrifuge tube and placed in an ultrasonic water bath at 20 kHz and 65 W; the ultrasonic wave is applied intermittently with a cycle of 10 s on and 10 s off, and the treated particles are collected every 1 min and spectrophotometrically determined at 600 nm.